2013
DOI: 10.1080/01609513.2012.753836
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of a Standards-Based Inventory of Foundation Competencies in Social Work with Groups

Abstract: However, surveys have reported that many group workers know little about the Standards or about how to teach or apply group work knowledge and skills. This article summarizes the research on the development of a reliable and valid inventory based on the Standards and an effective teaching strategy to improve learning about the Standards. The inventory and teaching method provide tools for advancing evidence-based practice and teaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The challenges the students experienced were consistent with what other scholars found. Macgowan (2012Macgowan ( , 2013 also demonstrated that students rated working in mandated groups and promoting group exploration of nonproductive norms when they arise to be among the most challenging group worker responsibilities. In this study, participants also identified the middle stage tasks of mediating conflict and identifying obstacles that interfere with the group's or its members' ability to reach goals to be among their most challenging skills.…”
Section: Discussion and Applications For Social Work Practicementioning
confidence: 98%
See 2 more Smart Citations
“…The challenges the students experienced were consistent with what other scholars found. Macgowan (2012Macgowan ( , 2013 also demonstrated that students rated working in mandated groups and promoting group exploration of nonproductive norms when they arise to be among the most challenging group worker responsibilities. In this study, participants also identified the middle stage tasks of mediating conflict and identifying obstacles that interfere with the group's or its members' ability to reach goals to be among their most challenging skills.…”
Section: Discussion and Applications For Social Work Practicementioning
confidence: 98%
“…Participants who matriculated in the new curriculum did better on the IC-SWG than students under the old curriculum. Group work scholars recommend that the Standards be part of social work with groups' curriculum (C. S. Cohen & Olshever, 2013;Macgowan, 2012Macgowan, , 2013Macgowan & Vakharia, 2012;Macgowan & Wong, 2015;Shera et al, 2013).…”
Section: Discussion and Applications For Social Work Practicementioning
confidence: 99%
See 1 more Smart Citation